The clinical significance of indeterminate pulmonary nodules in melanoma patients at baseline and during follow-up chest CT. (2019) - Soliman, Magdy; Petrella, Teresa; Tyrrell, Pascal; Wright, Frances; Look Hong, Nicole J.; Lu, Hua; Zezos, Petros; Jimenez-Juan, Laura; Oikonomou, Anastasia
Abstract: Objective: This study aims to determine an appropriate timeline to monitor indeterminate pulmonary nodules (IPN) in melanoma patients to confirm metastatic origin. Materials and Methods: 588 clinically non-metastatic melanoma patients underwent curative intent surgery during 3 years. Patients with baseline chest CT and at least one follow-up (FU) CT were retrospectively analyzed to assess for IPN. Patients with definitely benign nodules, metastases and non-melanoma malignancies were excluded. Change in volume from first to FU CT, initial diameter (D1) and volume (V1), distance from pleura, peripheral and perifissural location, density and clinical stage were evaluated. Nodules were volumetrically measured on CTs and were considered metastases if they increased in size between two CTs or if increase was accompanied by multiple new nodules or extrapulmonary metastases. Results: 148 patients were included. Two out of 243 baseline IPN detected in 70 patients, increased significantly in volume in 3 and 5 months and were proven metastases. During FU, 86% of 40 interval IPN detected in 28 patients, were proven metastases. Interval nodule (p < 0.0001, HR:243, CI:[57.32, 1033.74]), 3-month volume change (OR:1.023, CI:[1.014, 1.033]), V1 (OR:1.006, CI:[1.003, 1.009]), D1 (OR:1.424, CI:[1.23, 1.648]), distance from pleura (OR:1.03, CI:[1.003, 1.059]), and combined stage IIC + III (OR:11.29, CI:[1.514, 84.174]), were associated with increased risk for metastasis. 43%, 72% and 94% of patients with IPN were confirmed with metastases in the first FU CT at 3, 6 and 12 months respectively. Conclusion: Baseline IPN are most likely benign, while interval IPN are high risk for metastasis. Absence of volume increase of IPN within 6 months excluded metastasis in most patients.